Pengaruh Iklan, Harga Dan Brand Ambassador Shopee Terhadap Minat Beli Mahasiswa (Studi Pada Mahasiswa Manajemen Universitas Muhammadiyah Gresik) - Rizky Abi Fahriantama; Moh. Agung Surianto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the effect of advertising, price and brand ambassadors on student buying interest. The type of research used is quantitative research. The sampling technique used slovin with a total sample of 90 respondents. The population used in this study were management students at Muhamaddiyah Gresik University. The data analysis technique used in this study is a multiple linear method. The results of the analysis show that advertising has a significant effect on purchase intention, price has a significant effect on purchase intention and brandambassadors have a significant effect on purchase intention.